1993
DOI: 10.1080/07315724.1993.10718293
|View full text |Cite
|
Sign up to set email alerts
|

Dietary magnesium affects susceptibility of lipoproteins and tissues to peroxidation in rats.

Abstract: Magnesium (Mg)-deficient and control diets were pair-fed to weanling Wistar rats for 8 days. Plasma lipoproteins were separated into various density classes by sequential preparative ultracentrifugation. The extent of lipid peroxidation was measured in terms of thiobarbituric acid reactive substances in lipoproteins and tissue homogenates before or after iron-induced lipid peroxidation. Hyperlipemia in Mg-deficient rats was accompanied by increased oxidation of very-low-density lipoproteins and low-density lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(87 citation statements)
references
References 20 publications
5
81
0
1
Order By: Relevance
“…27 Also, there are reports that magnesium deficiency increases suscep- tibility of lipoproteins to peroxidation in rats. 28 Conversely, magnesium supplementation failed to reduce blood pressure in randomized trials among normotensive subjects, 7,29 and high-magnesium diets have been reported to increase rather than decrease the risk of stroke in hypertensive rats. 30 In a randomized trial in China, a multiple vitamin/mineral supplement containing 200 mg of magnesium reduced the risk of stroke among men, but this effect may have been due to 1 of the several other micronutrients included in the supplement.…”
Section: Ascherio Et Al September 22 1998 1201mentioning
confidence: 99%
“…27 Also, there are reports that magnesium deficiency increases suscep- tibility of lipoproteins to peroxidation in rats. 28 Conversely, magnesium supplementation failed to reduce blood pressure in randomized trials among normotensive subjects, 7,29 and high-magnesium diets have been reported to increase rather than decrease the risk of stroke in hypertensive rats. 30 In a randomized trial in China, a multiple vitamin/mineral supplement containing 200 mg of magnesium reduced the risk of stroke among men, but this effect may have been due to 1 of the several other micronutrients included in the supplement.…”
Section: Ascherio Et Al September 22 1998 1201mentioning
confidence: 99%
“…Plasma MDA Concentrations of basal plasma MDA were determined as thiobarbituric-reactive substances by a modified method of Ohkawa et al (1979) as previously described (Rayssiguier et al, 1993). The pink chromogen was extracted with n-butanol (4 ml), and its absorbance was measured at 532 nm by spectrophotometry (Perkin Elmer Cetus, Norwalk, CT, USA).…”
Section: Reagentmentioning
confidence: 99%
“…Cu deficiency not only increases serum cholesterol but also increases the susceptibility of very-low-density lipoprotein (VLDL) and LDL to in v i m Cu-induced oxidation (Rayssiguier et al 1993). These workers also found increased thiobarbituric acid-reactive substances in heart and liver tissues from Cu-deficient rats while Nelson et al (1992) found increased aortic lipid peroxides (malondialdehyde equivalents) in rats fed on Cu-marginal and Cu-deficient diets, the latter increase being associated with depressed aortic CuZn-SOD activity.…”
Section: Copper a N D Atherosclerosismentioning
confidence: 99%